Effects of Soil Structure Interaction on Reinforced Concrete Framed Structures - N. Dongol; s. Manandhar; P.M Pradhan (International Association of Lowland Technology, 2020)
This study proposes to highlight effects of soil structureinteraction on the Reinforced Concrete (RC) framedstructures. In this study, the seismic responses of thestructures are observed considering soil structureinteraction (SSI) from its actual soil condition. Here, twopreexisting structures are taken for the study. One isresidential building and the other is hospital building withtwo basements. Taking into account the actual soilcondition of each building site, this study provides idea onthe soil structure interaction on different kinds of buildings.Direct and substructure approaches are used to incorporatesoil structure interaction in the analysis. The properties ofsprings are calculated for different standard penetration test(SPT) values and springs are assigned for footing for thesubstructure approach. Entire soil-foundation-structuresystem is modelled and analyzed in single step for directapproach. Static analysis, response spectrum analysis andtime history analysis (THA) are done in order to find thevariations in natural periods, base shears and deflections ofthe structures by incorporating soil flexibility as compared tostructures with conventional fixed base.